PERAN COMPETITIVE ADVANTAGE MEMEDIASI PENGARUH DIGITAL MARKETING TERHADAP MARKETING PERFORMANCE PADA UMKM COFFEE SHOP - Sucitha, I Gede Adi; Giantari, I Gst. Ayu Kt.; Jaya Agung Widagda K., I Gst. Ngurah; Dana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The development of MSMEs in Indonesia is currently increasing, one of which is in the culinary field, namely coffee shops. This can be seen from the number of coffee shops or coffee shops that have sprung up in various cities in Indonesia, one of which is Denpasar City, which is located in the Province of Bali. A coffee shop is a place that is loved by many people from all walks of life, who puts various processed types of coffee as the main menu. This study aims to explain the role of competitive advantage in mediating the influence of digital marketing on marketing performance at MSME Coffee shops in Denpasar City. The population in this study are all MSME Coffee shops in Denpasar City whose numbers cannot be known. This research was conducted in Denpasar City with the number of samples taken as many as 60 business actors or respondents. The sample was determined using a non-probability sampling model, with a purposive sampling technique. The data analysis technique used is path analysis and Sobel test with SPSS for windows program. The results show that digital marketing has a positive and significant effect on marketing performance, digital marketing has a positive and significant effect on competitive advantage, competitive advantage has a positive and significant impact on marketing performance, competitive advantage is able to significantly mediate the influence of digital marketing on marketing performance.